Donor Unrestricted T Cells: Linking innate and adaptive immunity. Issue 50 (8th December 2021) - Soma, Shogo; Lewinsohn, Deborah A.; Lewinsohn, David M.
Abstract: Donor Unrestricted T Cells (DURTs) are characterized by their use of antigen presentation molecules that are often invariant. As these cells recognize diverse mycobacterial antigens, often found in BCG, these cells have the potential to either serve as targets for vaccination, or as a means to enable the induction of traditional T and B cell immunity. Here, we will review specific DURT family members, and their relationship to BCG.